EVALUATION OF ANTIOXIDANT ACTIVITY AND VALIDATED METHOD FOR ANALYSIS OF POLYPHENOLS FROM NON-EDIBLE PARTS OF INDIAN TROPICAL FRUITS BY USING MICROWAVE ASSISTED EXTRACTION AND LC-MS/MS - ANUBHUTI SHARMA,; PRITI GUPTA, (International Journal of Pharma and Bio Sciences, 2013)
Antioxidant activity and polyphenols were determined by Microwave assisted extraction technique (MAE) from non- edible parts of Indian tropical fruits. Antioxidant activity was performed using FRAP, ABTS and DPPH assays. Nine polyphenols were quantified by LC-MS/MS. Results showed that skin extract of A. comosus contained highest value for all antioxidant assays. Polyphenolic compounds were found highest in Carissa carandas pomace. In all the obtained extracts rutin was present as major flavonoid. Method was optimized and validated for the analysis of polyphenols as per the ICH requirement for analytical methods. To validate the matrix effects repeatability, reproducibility, recovery and overall uncertainty were calculated for the six matrices at 0.025, 0.050 and 0.100 µg gm-1 concentration. Recovery was ranged between 80.2 to 107% with RSD less than 15.0 %. Results suggest that MAE is a good alternative for extraction of polyphenols and provide significant advantages in terms of extraction efficiency and timesavings.